2020
DOI: 10.3389/fncel.2020.00048
|View full text |Cite
|
Sign up to set email alerts
|

A Brain Signaling Framework for Stress-Induced Depression and Ketamine Treatment Elucidated by Phosphoproteomics

Abstract: Depression is a common affective disorder characterized by significant and persistent low mood. Ketamine, an N-methyl-D-aspartate receptor (NMDAR) antagonist, is reported to have a rapid and durable antidepressant effect, but the mechanisms are unclear. Protein phosphorylation is a post-translational modification that plays a crucial role in cell signaling. Thus, we present a phosphoproteomics approach to investigate the mechanisms underlying stress-induced depression and the rapid antidepressant effect of ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Its relevance for depression research is due to the fact that dysregulation of the phosphoproteome is observed in MDD patients, as well as other CNS disorders (Martins- de-Souza et al, 2012;Morshed et al, 2021). Furthermore, phosphoproteomics analysis has been utilised to determine the acute molecular mechanism of action of antidepressant drugs such as ketamine (Xiao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its relevance for depression research is due to the fact that dysregulation of the phosphoproteome is observed in MDD patients, as well as other CNS disorders (Martins- de-Souza et al, 2012;Morshed et al, 2021). Furthermore, phosphoproteomics analysis has been utilised to determine the acute molecular mechanism of action of antidepressant drugs such as ketamine (Xiao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Inc, LA Jolla, USA). Size of treatment group numbers were based on prior studies (n=4-6) for a total of 21 samples (Mees, Li, et al, 2022; Mees, Tran, et al, 2022; Xiao et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the basal and CaM-stimulated PMCA activities were reduced in the synaptosomal membranes mainly due to a direct interaction of the drug within large catalytic loop and competing with CaM for binding in the C-terminal domain of the pump [ 87 , 88 ]. Similarly, emerging studies also suggest the interaction of ketamine with CaM-dependent enzymes, in particular CaMKII [ 89 , 90 ], but no specific functional studies largely limit the conclusions on CaM and PMCA-mediated Ca 2+ regulation in schizophrenia.…”
Section: Plasma Membrane Ca 2+ -Atpase (Pmca)—tmentioning
confidence: 99%
“…Environmental challenges or stressful events, such as chronic ultra-mild stress (CUMS), alter microRNAs (miRNAs) in the brain, including the hippocampus (9,10). MiRNAs are a class of small, noncoding RNAs able to mediate cleavage or translational repression of target mRNAs by binding preferentially to 3' untranslated regions (UTRs) (11).…”
Section: Introductionmentioning
confidence: 99%